Study of photovoltaic systems with differences connecting configuration topologies for applications in renewable energy systems - Mouhoub, Birane; Abdelghani, Chahmi (جامعة الوادي - university of el oued, 2019)
This paper focuses in the optimization of the efficiency of photovoltaic power conversion systems; we present a new alternative for improving both the optimization of the efficiency of photovoltaic power conversion chain. In this way, we present to the valuation problem of photovoltaic by new coupling systems between photovoltaic generators and their loads and performance of photovoltaic (PV) systems and the efficiency of the energy conversion by using different configuration of power converters. Different type’s improvements have been proposed of different architecture in order to choose the correct PV architecture for each PV installation on the efficiency improvement in all power conversion level stages between PV cells and loads. In this context, this work presents the study and adaptive simulation of photovoltaic systems with micro inverters configurations for applications of renewable energy. We performed comparative between a central and distribution connection of converter via an adaptation floor with Maximum Power Point Tracker (MPPT) control. For this reason, it is important to know different types of architecture and different configuration of power converters in order to choose the correct PV architecture for each PV installation. Simulation results are used to demonstrate the proposed topologies to provide improvement in efficiency over existing traditional PV systems.
Article
Keywords: Photovoltaic systems, Maximum Power Point Tracker MPPT, Topologies, micro inverters, performance, power, DC-DC Converters